Telaah Penerapan Kaidah Dilalah al-Faz ala al-Ahkam Terhadap Ayat-ayat Li’an Perspektif Hukum Islam dan Hukum Positif - Hibatullah, Alif; Kholid, Abd. (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2023)
Abstract: Currently, cases of infidelity leading to divorce are frequently encountered. In Islamic law, if a husband finds out about his wife’s adultery without any witnesses, they can resort to li’an based on the evidence from Surah al-Nur, verses 6-10. Similarly, in positive law, a husband can sue his wife for adultery. There arises a new issue concerning the status of children resulting from li’an in the perspectives of Islamic law and positive law, which exhibit differences. In the field of Quranic exegesis, understanding the content, intentions, and laws within Quranic verses is known as kajian dalalah al-fadh ala al-ahkam in the Quran. Furthermore, as Indonesian citizens, there's a bond with national laws. Therefore, this study examines from two viewpoints: Islamic law and positive law. The aim is to examine Quranic verses regarding li’an using the approach of dalalah al-fadh ala al-ahkam in the Quran and also from the perspective of positive law. The research method employed is descriptive qualitative through library research. The findings indicate that Surah al-Nur, verses 6-10, fall under dalalah al-ibarah as it distinctly reveals the purpose, intent, and law it encompasses, specifically the law of li’an In the perspective of Islamic law, the status of a couple engaged in li’an will be terminated, and there can be no reconciliation; the child resulting from li’an is not attributed to their biological father and does not inherit any rights from him. However, according to positive law, the proven adulterous party may face a maximum penalty of nine months' imprisonment, provided there's a report from the aggrieved party. The status of a couple involved in li’an is divorce, and reconciliation is not possible. The child from li’an can still be attributed to the biological father through legal means in positive law.Keywords: Alquran, Dalalah, Li’an, Positive Law.  Abstrak: Pada saat ini sering ditemui kasus perselingkuhan hingga menyebabkan perceraian. Sekiranya seorang suami mengetahui istrinya berzina sedangkan tidak ada saksi yang menyaksikannya maka dalam hukum Islam pasangan ini dapat melakukan li’an dengan dalil surat al-Nur ayat 6-10. Begitu juga dalam hukum positif, seorang suami dapat menggugat istrinya karena selingkuh. Terdapat masalah baru dalam status anak dari li’an dalam perspektif hukum Islam dan hukum positif yang memiliki perbedaan. Dalam kaidah tafsir untuk mengetahui kandungan maksud dan hukum dalam ayat Al-Qur’an dikenal dengan kajian dalalah al-fadz ala al-ahkam dalam Alquran. Selain itu sebagai warga negara Indonesia tentu terikat juga dengan undang-undang sehingga penelitian ini mengkaji dari dua perspektif, hukum Islam dan hukum positif. Penelitian ini bertujuan mengkaji ayat-ayat Alquran tentang li’an dengan pendekatan dalalah al-fadz ala al-ahkam dalam Alquran dan juga perspektif hukum positif. Metode yang dipakai artikel ini adalah kualitatif deskriptif dengan pendekatan library research. Hasil penelitian menunjukkan bahwa surat al-Nur ayat 6-10 termasuk dalalah al-ibarah karena terlihat jelas maksud, tujuan dan hukum yang dikandungnya yakni hukum li’an. Status pasangan yang li’an perspektif hukum Islam akan terputus dan tidak dapat rujuk selamanya, anak dari li’an tidak dinasabkan kepada bapak biologisnya dan tidak mendapat hak apapun darinya. Sedangkan menurut hukum positif pihak yang terbukti selingkuh mendapat hukuman paling lama sembilan bulan penjara dengan catatan ada laporan dari pihak yang dirugikan. Status pasangan yang terlibat li’an adalah cerai dan tidak bisa rujuk. Anak dari li’an masih bisa dinasabkan kepada bapak biologis dengan jalur hukum.Kata kunci: Alquran, Dalalah, li’an, Hukum Positif.